Applying Gain or Loss Framing in Promotional Email Messages to Encourage Event Attendance for Agricultural Educator Global Learning Professional Development - Megan LP Norman; Daniel Foster; Jessica Gall Myrick; Melanie Miller Foster (Journal of Applied Communications, 2025)
Encouraging agricultural educators to attend professional development events can be a challenge given that educators have many responsibilities and time commitments. Applying prospect theory to communication, we created gain or loss framed recruitment messages that encouraged participation in an online community dedicated to global agricultural educator empowerment to better understand what message designs may encourage participation. In an online experiment, participants were randomly assigned to view the loss or gain message that promoted a real, upcoming community event. The loss frame messages emphasized what participants would miss out on if they did not attend. Conversely, the gain frame highlighted the benefits of attending the event. We found no main effect of message frame (gain or loss) on attitudes toward the event or intentions to attend the event. We found a marginally significant result on efficacy perceptions, in which the loss frame engendered higher levels of efficacy to engage in the online community compared to the gain frame message. Moreover, involvement in the community (one’s existing perception that the community is important and relevant to them) predicted their event attitudes and intentions. Thus, one’s involvement with the organization mattered more than the message wording to promote an event in the context of this non-formal education event. Future research should explore what other message strategies may work to encourage overall participation and what other strategies work to specifically engage low involvement participants to attend agricultural professional development events.
Keywords: Gain or loss framing; prospect theory; message design; involvement